Prevalence of asthma, asthma-like and allergic symptoms in the urban, and rural adult, population in Eastern Turkey - Tug, T; Acik, Y (Allergy Immunol Soc Thailand,, 2002)
There is no study assessing the prevalence rates for asthma, asthma-like symptoms, and allergic symptoms in Eastern Turkey. In this study, we investigated these rates in the urban and rural adult population of Elazig Region in Eastern Turkey. A questionnaire was prepared based on the standard inquiry form of the European Community Respiratory Health Survey. The survey included 3,501 consented adults who were randomly selected. Each questionnaire was interviewed face-to-face by a physician. It was found that the cumulative prevalence rates of asthma and asthma-like symptoms of the rural and the urban respondent groups were 29.6% and 25.8%, respectively. The periodic prevalence rates of the same symptoms were 27.3% and 19.3%, respectively. The percentages of the patients living in rural and urban areas diagnosed as asthma by a physician were 5.5% and 3.1%, respectively. The proportions of patients with a history of at least one allergic disorder were 36.4% and. 23.7% in the rural and urban groups, respectively. Asthma and asthma-like symptoms in patients with allergic rhinoconjunctivitis were significantly higher than those without (p < 0.01). The cumulative rates of a previous diagnosis of asthma among respondents with a history of asthma-like symptoms were 18.4% in the rural and 11.2% in the urban groups (p < 0.05). Among those who had had periodic asthma-like symptoms, the rural and urban rates of previous asthma diagnosis were 18.6% and 14.3%, respectively (p < 0.01). Unexpectedly, the prevalence rates for asthma, asthma-like and allergic symptoms in adults living in the rural areas of Elazig Region in Eastern Turkey were significantly higher than the rates in the urban population.
Keywords: Severity